2021
DOI: 10.19044/esj.2021.v17n17p267
|View full text |Cite
|
Sign up to set email alerts
|

Effets des pratiques agroécologiques sur l’efficacité du système productif des producteurs maraîchers au sud du Bénin

Abstract: La production maraîchère au Bénin est associée à l’usage des intrants chimiques pour améliorer les rendements. Mais face aux risques environnementaux qui pèsent sur le milieu de production, il est nécessaire de produire plus écologique. L’objectif de cette étude est d’évaluer l’effet des pratiques agroécologiques sur l’efficience du système productif des maraîchers. A cet effet, une base de données du Centre VaLDERA renseignant sur les pratiques agricoles, comptes et résultats d‘exploitation de 197 producteurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
0
0
Order By: Relevance
“…Study showed that mineral fertilizer using had a significant effect on efficiency on farms. This result is consistent with Ahouangninou et al (2021) who observed that combine chemical and organic fertilizers allowed producers to increase their productivity, which is an expression of efficiency. This observation was also made by Dagbénonbakin et al (2012) who concluded that mixing compost with chemical fertilizer increases productivity unlike exclusive compost use which penalizes yields.…”
Section: Efficiency Strongly Correlated To Work and Mineral Manuresupporting
confidence: 92%
“…Study showed that mineral fertilizer using had a significant effect on efficiency on farms. This result is consistent with Ahouangninou et al (2021) who observed that combine chemical and organic fertilizers allowed producers to increase their productivity, which is an expression of efficiency. This observation was also made by Dagbénonbakin et al (2012) who concluded that mixing compost with chemical fertilizer increases productivity unlike exclusive compost use which penalizes yields.…”
Section: Efficiency Strongly Correlated To Work and Mineral Manuresupporting
confidence: 92%
“…Inappropriate use of ATB products is therefore one of the potential risk factors for exposure of milk producers and consumers to ATBs. The same observation was made in Benin (Ahouangninou et al, 2011), Senegal (Cissé et al, 2003), Ghana (Ntow et al, 2006Bempah et al, 2011) and Côte d'Ivoire (Doumbia and Kwadjo, 2009). The big problem with ATBs in West Africa lies in their free marketing (Ahouangninou et al, 2011).…”
Section: Discussionsupporting
confidence: 54%
“…One association reports a four-fold increase in the presence of DDT in Alzheimer's patients Mancozeb had the highest risks to human health with indices of 2289.8, respectively; 3537.8 and 3499.2 in the work of Houangninou et al [12]. Another study in Benin shows that lambda-cyhalothrin causes adverse effects in humans such as diarrhoea, nausea, etc., while acetamipride causes neurotoxic effects [28,29].…”
Section: Discussionmentioning
confidence: 99%